Perkiraan Pola Permintaan Paspor di Kantor Imigrasi dengan Menggunakan Metode Exponential Smoothing untuk Memaksimalkan Layanan - Riszki Fadillah; Fitriyani, Intan Nur; Ramadani, Putri; Mardivta, Hafizhah (Yayasan Literasi Sains Indonesia, 2025)
This study aims to analyze the passport application patterns at the Immigration Office and forecast the number of applications for the coming years using the Exponential Smoothing (Holt-Winters) model. The data used includes the number of passport applications from 2022 to 2024. The analysis shows a significant increase in applications in the coming years, with predictions for 2025, 2026, and 2027 indicating a consistent growth pattern. While the model demonstrates good accuracy, the Mean Absolute Error (MAE) and Root Mean Squared Error (RMSE) calculations indicate overestimation for the 2024 forecast. The application of the Holt-Winters model in forecasting passport applications in the Immigration field is a novel contribution to the literature, as this method is rarely used in this context. The model provides a systematic quantitative approach to predict long-term trends in application data, which is crucial for more efficient service capacity planning. The implications of these findings suggest that, although the model can predict a consistent growth pattern, the overestimation in 2024 highlights the need for model adjustment in the future. Therefore, increasing service capacity through additional staff and optimizing the digital queuing system are strategic steps that should be implemented to handle the projected surge in applications. These measures are essential to ensure efficient service and the Immigration Office's preparedness for the ongoing rise in applications.